Melphalan 140 mg/m2 or 200 mg/m2 for autologous transplantation in myeloma: results from the Collaboration to Collect Autologous Transplant Outcomes in Lymphoma and Myeloma (CALM) study. A report by the EBMT Chronic Malignancies Working Party - Auner, Holger W; Iacobelli, Simona; Sbianchi, Giulia; Knol-Bout, Cora; Blaise, Didier; Russell, Nigel H; Apperley, Jane F; Pohlreich, David; Browne, Paul V; Kobbe, Guido; Isaksson, Cecilia; Lenhoff, Stig; et al. (Haematologica, 2018)
Melphalan at a dose of 200 mg/m2 is standard conditioning prior to autologous hematopoietic stem cell transplantation for multiple myeloma, but a dose of 140 mg/m2 is often used in clinical practice in patients perceived to be at risk of excess toxicity. To determine whether melphalan 200 mg/m2 and melphalan 140 mg/m2 are equally effective and tolerable in clinically relevant patient subgroups we analyzed 1964 first single autologous transplantation episodes using a series of Cox proportional-hazards models. Overall survival, progression-free survival, cumulative incidence of relapse, non-relapse mortality, hematopoietic recovery and second primary malignancy rates were not significantly different between the melphalan 140 mg/m2 (n=245) and melphalan 200 mg/m2 (n=1719) groups. Multivariable subgroup analysis showed that disease status at transplantation interacted with overall survival, progression-free survival, and cumulative incidence of relapse, with a significant advantage associated with melphalan 200 mg/m2 in patients transplanted in less than partial response (adjusted hazard ratios for melphalan 200 mg/m2versus melphalan 140 mg/m2: 0.5, 0.54, and 0.56). In contrast, transplantation in very good partial or complete response significantly favored melphalan 140 mg/m2 for overall survival (adjusted hazard ratio: 2.02). Age, renal function, prior proteasome inhibitor treatment, gender, or Karnofsky score did not interact with overall/progression-free survival or relapse rate in the melphalan dose groups. There were no significant survival or relapse rate differences between melphalan 200 mg/m2 and melphalan 140 mg/m2 patients with high-risk or standard-risk chromosomal abnormalities. In conclusion, remission status at the time of transplantation may favor the use of melphalan 200 mg/m2 or melphalan 140 mg/m2 for key transplant outcomes (NCT01362972).
Keywords: recidiva; transplantace hematopoetických kmenových buněk; Humans; Transplantation, Autologous; lidé středního věku; analýza přežití; Hematopoietic Stem Cell Transplantation; Multiple Myeloma; Dose-Response Relationship, Drug; Female; Aged; příprava pacienta k transplantaci; dospělí; autologní transplantace; výsledek terapie; melfalan; senioři; lidé; Survival Analysis; mnohočetný myelom; Adult; Melphalan; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Transplantation Conditioning; Recurrence; vztah mezi dávkou a účinkem léčiva; mužské pohlaví